(untitled) (Texas Journal of Agriculture and Biological Sciences, 2023)
The article discusses the results of an experiment on the cultivation of licorice and its Phyto meliorative effect on the agrophysical and agrochemical properties of gray-meadow saline soils. It has been shown that licorice, used as a phytomeliorant, improves the overall physical properties of the soil and prevents the accumulation of water-soluble salts in the surface layers of the soil by lowering the groundwater level